(untitled) (Annals of Medical Research, 2024)
Aim: Knee osteoarthritis (KOA) is a prevalent chronic joint condition causing substantial pain and disability. In recent years, intra-articular injections of platelet-rich plasma (PRP), concentrated growth factor (CGF), and hyaluronic acid (HA) have emerged as promising KOA therapies. We aimed to compare the effects of intra-articular CGF, PRP, and HA in KOA patients. Materials and Methods: Patients diagnosed with KOA and who were grade 2-3 according to the Kellgreen-Lawrence classification in radiological imaging were included in the study. Patients were randomized into three groups receiving a single injection of either HA, PRP, or CGF. Patients were evaluated for pain scores using the visual analog scale (VAS) and for pain, stiffness, and physical function using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) before and 1 and 6 months after the procedure. Results: Of 60 patients, 41 were female and 19 were male. According to the Kellgren-Lawrence classification, 27 patients had grade II and 33 patients had grade III KOA, with a similar distribution among the three groups. The VAS scores showed a statistically significant decrease in all groups at 1-month and 6-month follow-up compared to pre-procedural scores. However, there was no significant difference among the groups in terms of VAS scores. The WOMAC-pain, -stiffness, -physical function scores also showed a significant decrease in all groups at 1-month and 6-month follow-up compared to pre-procedural scores. The CGF group had the lowest WOMAC scores at both time points, with a statistically significant difference compared to the PRP group (p<0.05). Patient satisfaction rates were high in all groups, while the satisfaction rate was highest in the CGF group. Conclusion: CGF demonstrated superior pain alleviation and functional improvement compared to PRP and HA. Although the results of this study demonstrate the potential of regenerative treatments for KOA, more research with larger samples and longer follow-up is needed for robust validation. Additionally, the standardization of treatment protocols is important.